Ion densities and magnetic signatures of dust pickup at Enceladus. Issue 4 (21st April 2014) - Kriegel, Hendrik; Simon, Sven; Meier, Patrick; Motschmann, Uwe; Saur, Joachim; Wennmacher, Alexandre; Strobel, Darrell F.; Dougherty, Michele K.
<x xml:space="preserve">Abstract</x> Encedalus' plume of charged dust has been shown to strongly modify the plasma structures. Therefore, we analyze the magnetic signatures of dust to constrain the dust plume. For the first time, the mutual feedback between the nanograins and their plasma environment is investigated. Our model combines plasma simulations by means of the A.I.K.E.F. (Adaptive Ion‐Kinetic Electron‐Fluid) code with Monte Carlo simulations of the 3‐D profiles of the gas and dust plumes. Data from several instruments of Cassini are considered: the neutral plume model is in good agreement with INMS data, whereas theoretical predictions of the peak ion density are compared against CAPS data, and properties of the dust are obtained by comparing our results with MAG data from the recent E14–E19 flybys. Our main results are (1) due to the ion‐neutral chemistry, H3O+ is the predominant ion species within the plume; (2) the high nanograin densities observed by CAPS require an increased effective ionization frequency to fulfill quasi‐neutrality; (3) the nanograin pickup current makes only a minor contribution to the current systems; i.e., the major contribution of the dust arises from electron absorption; (4) the pickup of nanograins is clearly visible in the magnetic field signatures, even including the distant encounter E15; (5) MAG data indicate a southward extension of the charged dust plume of at least 4 Enceladus radii; (6) the modification of the currents by the nanograins is responsible for the surprising fact that Cassini did not detect a region with a reduced magnetic field strength.